Cancer in the family: unveiling family members perceptions - Fernanda Visoná; Mariane Prevedello; Emiliane Nogueira de Souza (Universidade Federal de Santa Maria, 2012)
Objective: to describe the perception on immediate and extended family of a person diagnosed with cancer. Method: quantitative and qualitative study, involving family members who live with the patient during their treatment in the oncology ward of a hospital in Caxias do Sul, Rio Grande do Sul. Data was collected through semi-structured interviews and content analysis was performed subsequently. The project was approved by the Ethics Committee of the institution. Results: eighteen family members were interviewed. A cancer diagnosis has adverse effects on family members resulting in physical, psychological and social changes. Family members experience life style changes to get involved in overall care and remission-inducing treatment procedures. Conclusion: having someone diagnosed with cancer causes suffering and distress to family members and requires them to readjust their lifestyles